Smurf : A reliable method for contextualising social media artefacts - David, Anne (Cranfield University, 2020)
This research aims to evaluate whether artefacts other than the content of user com munication on social media can be used to attribute actions or relationships to a user. Social Media has enhanced the way users communicate on the Internet; providing the means for users to share content in real-time, and to establish connections and social relationships with like-minded individuals. However, as with all technology, social media can be leveraged for disagreeable and/or unlawful activities such as cyber bullying, trolling, grooming, or luring. There are reported cases where evidence from social media was used to secure convictions; for example, the tragic cases of Ashleigh Hall in 2009 and Kayleigh Haywood in 2015. The social media evidence e.g. the messages sent to the victim to arrange a meet up was used to link the suspect to the victim, and attribute actions to the suspect; in addition to other physical evidence presented as part of the case. Investigations with elements of social media is growing within digital forensics. This reinforces the need for a technique that can be used to make inferences about user actions and relationships, especially during a live triage investigation where the information needs to be obtained as quickly as possible. This research evaluates the use of live triage in the investigation of social media interactions, in order to determine the reliability of such a technique as a means of contextualising user activity, and attributing relationships or actions to a user. This research also evaluates the reliability of artefacts other than the actual content exchanged on social media; in the event that the content of communication is not immediately accessible/available to the investigator. To achieve this, it was important to break down the events that occur before, during and after user activity on social media; followed by the determination of what constitutes communication content in the context of this research. This research makes the following contributions: establishes a method for the cat egorisation of social media artefacts based on perceived user activity; communication content was characterised, thus highlighting evidential data of interest from user social media activity; the criteria for assessing the reliability of social media artefacts in a live triage investigation was proposed; a novel framework for social media investigation was developed with a Proof of Concept (PoC) to test its viability. The PoC demonstrates that it is possible to attribute actions or relationships to a user, using artefacts other than the actual content exchanged on social media.
© Cranfield University 2020. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Digital forensics; Social media; Live triage; User relationship